Lead in archived hair documents a decline in lead exposure to humans since the establishment of the US Environmental Protection Agency - Thure E. Cerling; Diego P. Fernandez; Ken R. Smith (Proceedings of the National Academy of Sciences, 2026)
Lead (Pb) is well known to be toxic to humans. We use archived hair from individuals living along the Wasatch Front in Utah to evaluate changes in exposure to lead over the last 100 y. Current concentrations of lead in hair from this population average almost 100 times lower than before the establishment of the Environmental Protection Agency. This low level of lead exposure is likely due to the environmental regulations established by Environmental Protection Agency.